Penyuluhan Hukum Partisipatif dalam Penyusunan Rancangan Peraturan Desa di Allang Asaude - Wattimury, Eivandro; Makaruku, Alfian Reymon (Penerbit Widina, Widina Media Utama, 2024)
The formulation of village regulations is crucial in promoting rural development and empowering village communities. Therefore, the available resources in the village must be managed effectively. In the effort to establish a competitive village, a comprehensive understanding of the process of drafting village regulations—both in their preliminary drafts and as finalized legal instruments—is essential for all village stakeholders. This community service initiative aimed to enhance understanding of the procedures for drafting legal products at the village level in accordance with the applicable laws and regulations. The implementation method consisted of three phases: preparation, execution, and evaluation. The outcomes of the program conducted in Allang Asaude Village, West Seram Regency, demonstrated a significant improvement in participants’ comprehension of the importance of village regulation drafting. Concretely, the activity succeeded in enhancing legal awareness among village officials and community members, and resulted in the development of a simplified draft village regulation as an initial output that may serve as a practical reference for future regulation-making processes.ABSTRAKPenyusunan peraturan desa sangat penting untuk mendorong pembangunan dan pemberdayaan masyarakat desa. Oleh karena itu, sumber daya yang ada di desa harus dikelola dengan sebaik-baiknya. Dalam upaya mewujudkan desa yang berdaya saing, dibutuhkan pemahaman yang memadai mengenai proses penyusunan peraturan desa, baik dalam bentuk rancangan maupun peraturan desa yang telah ditetapkan sebagai payung hukum bagi seluruh unsur di desa. Tujuan kegiatan pengabdian ini adalah untuk memberikan pemahaman tentang penyusunan produk hukum di tingkat desa sesuai dengan ketentuan peraturan perundang-undangan. Metode yang digunakan meliputi tiga tahap, yaitu: persiapan, pelaksanaan, dan evaluasi. Hasil dari kegiatan pengabdian yang dilaksanakan di Desa Allang Asaude, Kabupaten Seram Bagian Barat menunjukkan adanya peningkatan pemahaman para peserta terhadap pentingnya penyusunan peraturan desa. Secara konkret, kegiatan ini berhasil meningkatkan pemahaman masyarakat dan aparatur desa serta menghasilkan rancangan peraturan desa sederhana sebagai luaran awal yang dapat dijadikan pedoman dalam penyusunan peraturan desa di masa mendatang.